Stability Test and Antioxidant Activity Test of Sheet Mask Preparation of Avocado Peel (Persea americana Mill) Ethanol Extract with DPPH (2,2-Diphenyl-1-Pikrilhydrazil) method - Uswatun Khasanah; Yetti Hariningsih; Syamsul Ma'arif; Hery Prambudi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The avocado plant (Persea americana Mill) is known to have various benefits, one of which is in the skin of the fruit which contains flavonoid compounds as antioxidants. This antioxidant compound has the potential to be used as an active ingredient in various cosmetic preparations, one of which is sheet masks. This study aims to determine the physical quality, stability, and antioxidant activity of avocado peel ethanol extract formulated in sheet mask preparation. This study uses a quantitative method with an experimental design, and applies a complete random design (RAL) consisting of three variations of extract concentration, namely 2%, 4%, and 6%. Physical quality evaluation includes organoleptic, homogeneity, pH, adhesion, and viscosity, as well as stability tests using the cycling test methodÂ for six cycles. Antioxidant activity was tested using the DPPH method to determine the IC50 value. The results show that all formulas meet good physical quality. The 6% formula has the best stability with a pH of 5.79±0.062, an adhesion of 3.60 ± 0.130 seconds, and a viscosity of 9490.67 ± 27.57 cP. Statistical tests showed no significant changes in pH (p = 0.385), adhesion (p = 0.833), and viscosity (p = 1.000). The antioxidant activity test showed that Sheet mask with a concentration of 6% had an IC50 value of 198.11 ppm and was classified as having weak antioxidant activity, while avocado peel ethanol extract had an IC50 value of 53.11 ppm and was classified as having strong antioxidant activity. So it can be concluded that sheet mask preparations have good physical quality and are stable during storage, but the antioxidant activity of avocado peel extract is higher than sheet mask preparations.